2016
DOI: 10.3390/w8110528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slope, Rainfall Intensity and Mulch on Erosion and Infiltration under Simulated Rain on Purple Soil of South-Western Sichuan Province, China

Abstract: Purple soil is widely distributed in the hilly areas of the Sichuan basin, southwest China, and is highly susceptible to water erosion. The triggering of this process is related to slope, rainfall intensity and surface cover. Therefore, this study assesses the effects of different simulated rainfall intensities with different slopes on hydrological and erosional processes in un-mulched and mulched purple soils. Results show that the sediment and water losses increased with an increase of rainfall intensity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 74 publications
5
27
0
Order By: Relevance
“…Figure 1 indicates that runoff is further exacerbated by increases in rainfall intensity. These results are in line with findings by Khan et al [24], who reported an increase in sediment and water loss with an increase in rainfall intensity and slope steepness, in a laboratory experiment conducted under rainfall simulation using Calcaric Regosols. Xin et al [25] also conducted a laboratory rainfall simulation experiment using black soils (Udic Argiboroll) at 7% fixed slope, five levels of residue cover (bare, 15%, 35%, 55%, and 75%) and four rainfall intensities (30 mm/h, 60 mm/h, 90 mm/h, and 120 mm/h).…”
Section: Soil Degradation: the Biggest Threat In Agriculturesupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 1 indicates that runoff is further exacerbated by increases in rainfall intensity. These results are in line with findings by Khan et al [24], who reported an increase in sediment and water loss with an increase in rainfall intensity and slope steepness, in a laboratory experiment conducted under rainfall simulation using Calcaric Regosols. Xin et al [25] also conducted a laboratory rainfall simulation experiment using black soils (Udic Argiboroll) at 7% fixed slope, five levels of residue cover (bare, 15%, 35%, 55%, and 75%) and four rainfall intensities (30 mm/h, 60 mm/h, 90 mm/h, and 120 mm/h).…”
Section: Soil Degradation: the Biggest Threat In Agriculturesupporting
confidence: 93%
“…The kinetic energy impact of raindrops on soil surface in high intensity storms causes increased soil particle detachment and sediment loss, excess runoff and surface sealing [23]. According to Khan et al [24], the triggering of this process is related to slope, rainfall intensity and surface cover. The detached soil particles are transported away from the site of drop impact through runoff, which exacerbates land degradation [1,5].…”
Section: Soil Degradation: the Biggest Threat In Agriculturementioning
confidence: 99%
“…As moisture content increases, the infiltration value decreases, until it reaches its theoretical minimum, which is dependent on the soil texture and structure. In reality, this minimum value is not a constant but rather a function of rainfall intensity [17]. Higher rainfall intensity triggers a higher final infiltration rate, as described by Rose [18].…”
Section: Introductionmentioning
confidence: 93%
“…It might be because forested soil has stronger and more persistent water repellency due to the high organic matter contents under dry conditions [41]. In addition, the steep slope gradients of the forest as compared to the pasture could have played a role, which results in a shorter time for water remaining on the soil because of the gravity effect lower water storage capacity on steep slopes [42]. However, it should be noted that the subsurface flow and total streamflow in FW were both higher than AW.…”
Section: Coupled Effects Of Land Use and Topography On Streamflow Varmentioning
confidence: 99%